Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/ijc.23455
|View full text |Cite
|
Sign up to set email alerts
|

Gain of 1q21 and distinct adverse cytogenetic abnormalities correlate with increased microcirculation in multiple myeloma

Abstract: To identify genetic mechanisms controlling bone marrow microcirculation and angiogenesis in patients with plasma cell disease we simultaneously performed bone marrow dynamic contrastenhanced magnetic resonance imaging (DCE-MRI) and cytogenetics (iFISH) on CD138 purified plasma cells of MGUS (n531) and untreated multiple myeloma (MM) (n 5 87) patients. The adverse cytogenetic abnormalities gain of 1q21, deletion 17p13 and deletion 13q14 significantly correlated with at least one DCE-MRI finding (aberrant ''foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
3
7
0
1
Order By: Relevance
“…We found that patients with a diffuse MRI pattern had a higher incidence of high risk cytogenetic features, including del17p, add1q21, and del 13q compared to patients with focal or normal MRI patterns. This result is described for the first time and is in accordance with a recent observation of the Heidelberg group in 87 untreated myeloma patients where the gain of 1q21 and the deletions of 17p and 13q significantly correlated with at least one abnormal finding in bone marrow dynamic contrastenhanced MRI, that is, aberrant ''focal'' microcirculation pattern, increase in median microcirculation parameter amplitude A or exchange rate constant kep, suggesting that these chromosomal abnormalities trigger the angiogenic cascade in MM [14]. Indeed, our group has described that patients with diffuse MRI pattern have increased microvessel density in their trephine biopsies and adverse myeloma features [5].…”
Section: Mri Patterns and Cytogenetic Abnormalitiessupporting
confidence: 91%
“…We found that patients with a diffuse MRI pattern had a higher incidence of high risk cytogenetic features, including del17p, add1q21, and del 13q compared to patients with focal or normal MRI patterns. This result is described for the first time and is in accordance with a recent observation of the Heidelberg group in 87 untreated myeloma patients where the gain of 1q21 and the deletions of 17p and 13q significantly correlated with at least one abnormal finding in bone marrow dynamic contrastenhanced MRI, that is, aberrant ''focal'' microcirculation pattern, increase in median microcirculation parameter amplitude A or exchange rate constant kep, suggesting that these chromosomal abnormalities trigger the angiogenic cascade in MM [14]. Indeed, our group has described that patients with diffuse MRI pattern have increased microvessel density in their trephine biopsies and adverse myeloma features [5].…”
Section: Mri Patterns and Cytogenetic Abnormalitiessupporting
confidence: 91%
“…Different patterns of bone marrow involvement of MM in conventional as well as DCE-MRI have been described concordantly by different authors (14,23,29,30). Diffuse distribution of microcirculation was found in healthy controls as well as in all stages of plasma cell disease.…”
Section: Discussionsupporting
confidence: 56%
“…33 Two model variables are used to describe the tissue-specific information of the signal intensity-time curves: amplitude A (arbitrary units) is proportional to the relative signal enhancement as a surrogate for MVD and perfusion, the exchange rate constant kep (minutes) reflects the contrast agent transit between the extravascular and intravascular compartment.…”
Section: In Vivo Assessment Of Angiogenesis By Dynamic Contrast-enhanmentioning
confidence: 99%